Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L M; Bautista, L M; Lázaro, E (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork

Nest-site selection and nesting success in the Azure-winged Magpie in Central Spain - Alonso, J A; Muñoz-Pulido, R; Bautista, L M; Alonso, J C (Bird Study, 1991)
Nest-site selection and nesting success in Azure-winged Magpies Cyanopica cyana were studied in 1986 in central Spain. Preferred nest sites were a nonrandom subset of the available habitat. Nests built on evergreen trees had significantly earlier clutch initiation dates than those built on deciduous trees. Birds selected larger trees of each species for nesting, but nests built on very high trees had significantly lower nesting success. Birds tended to locate their nests in a central position relative to the canopy height and as far from the main trunk as possible, without being of the periphery. This may minimize nest accessibility and maximize concealment. Nesting success was higher in the preferred regions of the tree canopy. Predation and inclement weather were probably the factors selecting for the observed patterns in nest-site distribution.
doi: 10.1080/00063659109477066
Keywords: Canopy; Cyanopica cyana; Evergreen and deciduous species (voyant); Nest site selection; Nesting success